Caprine brucellosis: A historically neglected disease with significant impact on public health. - Carlos A Rossetti; Angela M Arenas-Gamboa; Estefanía Maurizio (Public Library of Science (PLoS), 2017)
Caprine brucellosis is a chronic infectious disease caused by the gram-negative cocci-bacillus Brucella melitensis. Middle- to late-term abortion, stillbirths, and the delivery of weak offspring are the characteristic clinical signs of the disease that is associated with an extensive negative impact in a flock's productivity. B. melitensis is also the most virulent Brucella species for humans, responsible for a severely debilitating and disabling illness that results in high morbidity with intermittent fever, chills, sweats, weakness, myalgia, abortion, osteoarticular complications, endocarditis, depression, anorexia, and low mortality. Historical observations indicate that goats have been the hosts of B. melitensis for centuries; but around 1905, the Greek physician Themistokles Zammit was able to build the epidemiological link between "Malta fever" and the consumption of goat milk. While the disease has been successfully managed in most industrialized countries, it remains a significant burden on goat and human health in the Mediterranean region, the Middle East, Central and Southeast Asia (including India and China), sub-Saharan Africa, and certain areas in Latin America, where approximately 3.5 billion people live at risk. In this review, we describe a historical evolution of the disease, highlight the current worldwide distribution, and estimate (by simple formula) the approximate costs of brucellosis outbreaks to meat- and milk-producing farms and the economic losses associated with the disease in humans. Successful control leading to eradication of caprine brucellosis in the developing world will require a coordinated Global One Health approach involving active involvement of human and animal health efforts to enhance public health and improve livestock productivity.